(untitled) (Journal of the College of Education for Women, 2019)
The present paper talks about balance between two poems which are the Nouniya for Ibn Zaidoun and Andalusia for Ahmed Shawqi. This study is not claimed to be the first of its kind but we found some artistic aspects that deserve to stop at them. This what makes the two the focus of critics and scholars as well in addition to their emphasis on the unity of the human feelings and immortality through the poet’s ability to employ those feelings and emotions in a way that it can express the human soul in every time and place. That is what we believe Ibn Zaidoun had reached in his poem. Therefore, the present paper has come into the conclusion that Ibn Zaydoon’s Nouniya is better than Shawqi’s Andalusia due to what we got through reading and analyzing an aspect of their poems. This preference can be summed up as follows:- Ibn Zaidoun adopted the style of irony and holding diodes which is based on antimony and contrast between opposite sides in the poem (perhaps the expression through paradox is connected to the argumentative situation, time and the conflict through which it falls into)1. Therefore, the language of Ibn Zaidoun relying on irony in manifesting the psychological meaning in a complete picture is coupled a lot with the human action whichdraws its continuation through time and this has given it human dimensions and a continuous argumentation.- The language of Ibn Zaidoun is a coherent language that expresses the nature of his era as he managed to adapt it to fit the emotional purposes that he wanted to express. Shawqi on the other hand used expressions that belonged to the pre-Islamic era. This forced us to go back to the dictionary to find out the meanings , i. e. , he did not bend the words to acquire new connotations so as to contribute to the development of the situation and content, a point to be considered for the poet.- The poem of Ibn Zaidoun represented an integrated thematic unit from the beginning till the end, while Shawqi’s poem was divided into sections, starting with parking on the ruins, descriptive parts, monologues, and conclusion.The symbol in Ibn Zaidoun’s poem acquired human dimensions, while Shawqi was characterized by locality in that the Sphinx symbolism was associated with Egypt. This is not compared to the beloved that expresses comprehensive human positions in every time and place. The symbol of the beloved for Ibn Zaidoun includes the entire poem while is confined to limited lines for Shawqi.